2018
DOI: 10.15208/beh.2018.58
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and dividend payout ratio in non-financial firms listed in Indonesian Stock Exchange

Abstract: Dividend payout policy has proved to be a complicated issue in the financial management literature that leads to the issuance of different arguments and theories explaining the facts about dividend ratio. The prime objective of the current study is to explore the impact of corporate governance on dividend payout ratio. In order to investigate the linkage between corporate governance and dividend payout ratio, data of four fiscal years (2013-2016) was extracted from annual reports of Indonesian publicly listed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
(25 reference statements)
2
8
0
3
Order By: Relevance
“…Morealso, There exists a positive (10.497) insignificant (t=0.38) relationship between ownership structure and dividend payout ratio in quoted manufacturing firms in sub-sahara Africa. This corroborates with a study led by Sumail [29], Hong et al [30] observed a positive relationship between ownership structure and dividend payout. Conversely, [25] shows that ownership structure has significant positive effect on dividend policy of the firm.…”
Section: Discussion and Interpretation Of Findingssupporting
confidence: 92%
“…Morealso, There exists a positive (10.497) insignificant (t=0.38) relationship between ownership structure and dividend payout ratio in quoted manufacturing firms in sub-sahara Africa. This corroborates with a study led by Sumail [29], Hong et al [30] observed a positive relationship between ownership structure and dividend payout. Conversely, [25] shows that ownership structure has significant positive effect on dividend policy of the firm.…”
Section: Discussion and Interpretation Of Findingssupporting
confidence: 92%
“…Dapat disimpulkan bahwa kepemilikan institusional berpengaruh positif dan signifikan terhadap kebijakan dividen. Pernyataan tersebut sejalan dengan penelitian yang dilakukan oleh Cheng et al (2018), Sindhu et al (2016), Jabeen dan Ahmad (2019), Widyastuti (2018), Aliyu et al (2016), Jacob & Jijo Lukose (2018, Jory et al (2017), Sumail (2018, Sumartha (2016), Miko & Kamardin (2015).…”
Section: Tabel 4 Uji Koefisien Determinasiunclassified
“…Menurut Tahir et al (2020), ini membuktikan teori outcome, dimana perusahaan dengan tata kelola yang bagus akan membagikan dividen lebih tinggi. Pengaruh positif juga disimpulkan dalam penelitian Kilincarslan dan Ozdemir (2018), Sumail (2018)…”
Section: Ukuran Direksi Dan Kebijakan Dividenunclassified